FARMER INNOVATIVENESS AND ITS IMPACT ON INTERNET AND SOCIAL MEDIA ADOPTION - Ćirić, Maja; Carić, Marko; Kuzman, Boris (Economics of Agriculture, 2018)
In recent years, huge efforts have been made to implement ICT innovations in the agricultural sector in order to increase its competitiveness. The question that can be posed is what depends on the successful implementation of ICT innovations among farmers. Numerous scientific papers were published with the purpose of identifying factors that affect acceptance of particular innovation by users. The aim of this paper was to determine whether the farmer innovativeness influences the acceptance and the degree of using the Internet and social media by farmer. Additionally, statistically significant correlation between the demographic factors of the farmers and their innovativeness was investigated. The research was conducted using survey method. Descriptive statistics, Correlation analysis using Pearsons correlation coefficients and Chi-square test were used as statistical methods. Obtained results confirmed the initial hypotheses and based on that recommendations for the creation of a marketing strategy for introducing new ICT solutions in the fled of agriculture are made.